Sustainability and Technology Use in SMEs: A Pathway to Green Innovation : Keberlanjutan dan Penggunaan Teknologi pada UMKM: Jalan Menuju Inovasi Ramah Lingkungan - Rieki Indra Bratamanggala; Yayan Hendayana (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study examines the critical role of green innovation and technology adoption in small and medium enterprises (SMEs) as pathways to sustainability. With increasing pressure from consumers and regulatory bodies for environmentally responsible practices, SMEs are facing both challenges and opportunities in implementing sustainable technologies. The research highlights key barriers such as high initial costs and limited technological knowledge, alongside the potential long-term benefits, including cost savings and enhanced competitiveness. Utilizing a systematic literature review, this paper identifies strategies for overcoming these barriers, emphasizing the importance of integrating green technologies into business models. Moreover, the findings suggest that government support, including subsidies and training, is essential for fostering an ecosystem conducive to sustainable innovation. The study concludes that by embracing green innovation, SMEs can not only comply with environmental standards but also differentiate themselves in the market, ultimately contributing to global sustainability goals.